Analisis Kemampuan Komunikasi Matematis Siswa SMP Ditinjau dari Self Efficacy pada Model Pembelajaran SQ4R dengan Project Assessment - Nahlati, Nanik; Widodo, Sri Adi; I, Istiqomah (LPPM Universitas Terbuka, 2023)
The purpose of conducting this research is to; 1) Describe students' mathematical communication skills in terms of self-efficacy at a high level with SQ4R learning with project assessment; 2) Describe students' mathematical communication abilities seen from self-efficacy at a moderate level with SQ4R learning with project assessment; 3) Describe students' mathematical communication abilities seen from self-efficacy at a low level with SQ4R learning with project assessment. This research is a qualitative research, and uses a qualitative descriptive method. The subjects in this study were class VIII E students of SMP Negeri 1 Banguntapan. Data collection techniques in this study used triangulation or a combination technique, namely through tests, questionnaires, and interviews. The results showed that 1) Students with a high level of self-efficacy were able to master the three indicators of mathematical communication skills, namely indicators 1, 2 and 3 on questions 1, 2, 3, 4 and 5; 2) students who have moderate self-efficacy are able to master two indicators of mathematical communication skills, namely indicators 1 and 3 in question numbers 1, 2, 3, 4, and 5, 3) students with low self-efficacy are able to master two indicators, namely indicators 2 and 3 in questions 4 and 5